2016
DOI: 10.1590/0037-8682-0114-2016
|View full text |Cite
|
Sign up to set email alerts
|

First report of TEM-104-, SHV-99-, SHV-108-, and SHV-110-producing Klebsiella pneumoniae from Iran

Abstract: Introduction: Extended-spectrum beta-lactamases (ESBLs) are bacterial enzymes capable of hydrolyzing beta-lactams. The aim of this study was to describe the prevalence of TEM-and SHV-type ESBL-producing Klebsiella pneumoniae strains in Zahedan, Southeast Iran. Methods: A total of 170 non-repetitive K. pneumoniae strains were collected from patients referred to three teaching hospitals of Zahedan. Antibiotic susceptibility testing was determined for 17 antibiotics using the Kirby-Bauer disc diffusion method. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
2
2
1
Order By: Relevance
“…To the best of our knowledge, this is the second report of bla IMP -harbored K. pneumoniae from Iran after Khorvash et al [27]. This study showed a high prevalence of ESBLs-encoding genes (bla SHV , bla CTX-M , and bla TEM ) among CRKP isolates, which is consistent with other studies conducted in Isfahan [25,26] and Iran [28][29][30]. However, we have not detected bla KPC , bla GES , bla IMI , and bla VIM among CRKP isolates.…”
Section: Discussionsupporting
confidence: 90%
“…To the best of our knowledge, this is the second report of bla IMP -harbored K. pneumoniae from Iran after Khorvash et al [27]. This study showed a high prevalence of ESBLs-encoding genes (bla SHV , bla CTX-M , and bla TEM ) among CRKP isolates, which is consistent with other studies conducted in Isfahan [25,26] and Iran [28][29][30]. However, we have not detected bla KPC , bla GES , bla IMI , and bla VIM among CRKP isolates.…”
Section: Discussionsupporting
confidence: 90%
“…ESBL-producing K. pneumoniae isolates are of great concern, both in treatment and in management of nosocomial infections. As multiple resistance genes mostly reside The frequency of ESBL-producing K. pneumoniae isolates was higher in this study than in some previous Iranian studies (16)(17)(18). However, higher frequencies were reported by Mahmoudi et (19,20).…”
Section: Discussioncontrasting
confidence: 66%
“…In addition, the present study demonstrated that the blaTEM type β-lactamase gene was the most prevalent ESBL gene in UPEC, which is consistent with the findings of several previously published studies (27)(28)(29)(30). In Italy (45.4%) [31], Portugal (40.9%) [32], and Turkey (72.7%), the blaTEM type βlactamase gene was the most prevalent [33].…”
Section: Discussionsupporting
confidence: 92%